Analysis of Factors Affecting Consumer Demand - Syamril, S.; Herman, H.; Arsyad, Muhammad (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
The objectives of this study are (1) To determine the effect of price and income partially on consumer demand and (2) To simultaneously determine the effect of price and income on consumer demand. This research is a quantitative study with two independent variables and one dependent variable with the test tools to be used, namely (1) validity test, (2) reliability test, (3) multiple linear regression test, t-test (partial), and f-test (Simultaneous). The sample used in this study was 96 respondents. Processing research data using multiple linear regression with SPSS version 24.0 software tools to read the direction of the influence of the independent variable on the dependent variable partially t-test and f-test. The results showed that price partially affects consumer demand. Income has a partially significant effect on consumer demand. The results show that price and income significantly affect consumer demand.